A Radical Revolution for Trifluoromethoxylation. Issue 27 (11th June 2018) - Sahoo, Basudev; Hopkinson, Matthew N.
Abstract : The study of OCF3 ‐substituted molecules is somewhat hampered by a lack of diverse synthetic methods to access them. By introducing a new mild and practical reaction system for accessing the . OCF3 radical, a recent study by Liu, Ngai, and co‐workers has the potential to dramatically expand the scope of direct trifluoromethoxylation. The features of this ground‐breaking system are discussed and placed into context with other recent advances on nucleophilic trifluoromethoxylation.